Answer:
Step-by-step explanation:
Exponential functions have a horizontal asymptote. The equation of the horizontal asymptote is
y
=
0
.
Horizontal Asymptote:
y
=
0
Answer:
y = - 2x + 1
Step-by-step explanation:
Substitute an x value from the table into the equation
x = 1 : y = - 2(1) = - 2 ← require to add 1 to obtain y = - 1
x = 4 : y = - 2(4) = - 8 ← require to add 1 yo obtain y = - 7
Then equation describing the relationship is
y = - 2x + 1
<h2>
Answer:</h2><h2>Plagiarism is when you take someones else's work and say it your own when its not. Without giving credit from your source that you used, that is considered plagiarism.</h2><h2 /><h2>Hope this helps!!</h2>
Answer:
5?
Step-by-step explanation:
I think you would count the middle point. But i don't completely know...
Answer:
$234
Step-by-step explanation:
because they did.....